Investigating Developer Experience in Software Reuse - Gonçalves, Rodrigo Feitosa; Werner, Cláudia Maria Lima; Farias, Claudio Miceli de (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2024: Anais do XVIII Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de SoftwareDO - 10.5753/sbcars.2024.3865, 2024)
Software reuse has been recognized as a key strategy for improving productivity, reducing development costs, and enhancing software quality. However, successfully implementing software reuse practices largely depends on the developer experience (DX). This study investigates the factors, barriers, and strategies influencing DX in software reuse. Through a Rapid Review (RR), we analyzed 328 studies, selecting 10 for detailed data extraction based on defined filters and the backward snowballing technique. Our findings identify 15 factors affecting DX in software reuse, categorized into technical, organizational, and human/social factors. We also uncover 7 barriers that impede developers from improving DX and identify 13 strategies to enhance it. The results highlight the critical role of comprehensive documentation, a clear understanding of software functionality, and robust reuse-compatible infrastructure as key technical factors. Organizational support, effective resource allocation, and fostering a communication, collaboration, and self-efficacy culture are essential for successful software reuse. This study’s insights have significant implications for researchers and practitioners, offering practical guidance to develop more effective reuse practices and improve DX.